Evaluating the impact of emotional regulation on the pedagogical communication skills of students in educational training universities: Evidence from quantitative analysis - Dao Thi Thu, Thuy; Vu Thuy, Hoan; Nguyen Thi Thu, Thuy; Tran Thi , Yen (Journal of Interdisciplinary Studies in Education, 2026)
The study examines how these strategies affect three core components of pedagogical communication skills: establishing and maintaining communication relationships, exchanging cognitive, emotional, and behavioral information, and using language and communication tools. A survey was conducted with 352 students currently studying at 6 universities in Vietnam. The results show that cognitive reassessment had the strongest impact on communication skills and language use (β = 0.610). In contrast, emotional repression had the strongest effect on relationship-building and maintenance skills (β = 0.531). Therefore, the study provides empirical evidence that emotional regulation and pedagogical communication competence are two distinct but closely related constructs.